Pengaruh Jumlah Permintaan, Omzet dan Harga terhadap Jumlah Produksi Pestisida pada PT Dharma Guna Wibawa di Jawa Timur - Lasmanto, Lasmanto; Lailatul, Nurul (KUBIS, 2022)
PT Dharma Guna Wibawa sells superior agricultural products in the form of pesticides. Companies with the aim of improving the rural economy for the better. With this company promotion is more focused on rural areas. As a company, PT Dharma Guna Wibawa cannot allow its production system to be carried out without any goods coming out of the company as a turnover to be reprocessed into capital. If the production demand exceeds the company's capacity, it will have a negative impact when consumer demand is realized. The analytical method used in this study is multiple linear regression with the dependent variable the amount of production and the independent variables include the number of requests, turnover and prices. The results of the model analysis in this study state that the variables Amount of Demand (X1), Turnover (X2) and Price (X3) have an effect on the total production value. Partially the variable X1 or the number of requests has a significant influence, this is because the value or amount of production is determined from the number of requests received each month. The X2 variable or the amount of turnover has an influence on the production value. An interesting fact in this study is that the variable X3 or price does not significantly affect the production value.